Global steam coal supply costs in the face of Chinese infrastructure investment decisions - Moritz Paulus; Johannes Trueby (Institute of Energy Economics at the University of Cologne (EWI), 2010)
In this work we demonstrate the effects of different Chinese transport infrastructure investment strategies on long run marginal costs of steam coal supply in Europe. Increasing Chinese demand for steam coal will lead to a growing need for additional domestic infrastructure in China as production hubs and demand centers are spatially separated. If domestic transport capacity is only available at elevated costs, Chinese power generators could turn to the global trade markets and increase steam coal imports. Increased Chinese imports could significantly influence global trade market price levels which would especially affect nations mainly relying on imports, like for example Europe. We analyze the scope of this effect under different assumptions for Chinese transport infrastructure developments. For this purpose, we develop a spatial equilibrium model for the global steam coal market. For our assumption regarding production and transport cost evolutions, we rely on an input factor-based cost calculation methodology. We find out that the investigated Chinese infrastructure decisions have a modest impact on long run marginal costs of supply for Europe and the US but significant effects for China.
Keywords: L94; L92; C61; Q30; 330; Steam coal; MCP; non-linear optimization; China; Europe; transport infrastructure; Kohle; Angebot; Grenzkosten; Import; Europa; USA; Verkehrsinfrastruktur; Verkehrsinvestition; China